Toward a Theory of Entrepreneurial Cognition: Rethinking the People Side of Entrepreneurship Research - Mitchell, Ronald K.; Busenitz, Lowell; Lant, Theresa; McDougall, Patricia P.; Morse, Eric A.; Smith, J. Brock (Entrepreneurship Theory and Practice, 2002)
The failure of past “entrepreneurial personality”—based research to clearly distinguish the unique contributions to the entrepreneurial process of entrepreneurs as people, has created a vacuum within the entrepreneurship literature that has been waiting to be filled. Recently, the application of ideas and concepts from cognitive science has gained currency within entrepreneurship research, as evidenced by the growing accumulation of successful studies framed in entrepreneurial cognition terms. In this article we reexamine “the people side of entrepreneurship” by summarizing the state of play within the entrepreneurial cognition research stream, and by integrating the five articles accepted for publication in this special issue into this ongoing narrative. We believe that the constructs, variables, and proposed relationships under development within the cognitive perspective offer research concepts and techniques that are well suited to the analysis of problems that require better explanations of the contributions to entrepreneurship that are distinctly human.